Less Invasive Surfactant Administration Reduces the Need for Mechanical Ventilation in Preterm Infants - Christine S. M. Lau MD; Ronald S. Chamberlain MD, MPA, FACS; Shyan Sun MD, DCH, FAAP (SAGE Publishing, 2017)
Neonatal respiratory distress syndrome due to surfactant deficiency is associated with high morbidity and mortality in preterm infants, and the use of less invasive surfactant administration (LISA) has been increasingly studied. This meta-analysis found that LISA via thin catheter significantly reduced the need for mechanical ventilation within the first 72 hours (relative risk [RR] = 0.677; P = .021), duration of mechanical ventilation (difference in means [MD] = −39.302 hours; P < .001), duration of supplemental oxygen (MD = −68.874 hours; P < .001), and duration of nasal continuous positive airway pressure (nCPAP; MD = −28.423 hours; P = .010). A trend toward a reduction in the incidence of bronchopulmonary dysplasia was observed (RR = 0.656; P = .141). No significant difference in overall mortality, incidence of pneumothorax, or successful first attempts was observed. LISA via thin catheter significantly reduces the need for mechanical ventilation within the first 72 hours as well as the duration of mechanical ventilation, supplemental oxygen, and nCPAP. LISA via thin catheter appears promising in improving preterm infant outcomes.